Artificial intelligence and changes in information practices in higher education: An exploratory study - Westbye, Hilde; Gasparini, Andrea Alessandro; Gullbekk, Eystein (Septentrio Conference Series, 2023)
Searching, evaluating, using, sharing and organizing information are central activities in writing and research processes. These activities are carried out by students who participate in the communities of practice they share with fellow students, teachers and supervisors. In today's changing landscape, the infrastructures surrounding the research process are changing, and both students and researchers make use of new aids that challenge established practices and open up innovative ways of thinking, researching and studying.In this poster, we examine how the introduction of artificial intelligence-based technology affects information practices in the context of learning and research in higher education, as well as how university libraries can be partners in this change. We base ourselves on an exploratory study that looks at a group of master's students and their use of AI-based tools in the writing process, and in particular on a tool for recommending literature called Keenious.The study involved interviews with the students in their last semester before submitting the master's thesis. We found that the students use different tools in the writing process and that in searching for literature they particularly used Google and Google Scholar, as well as recommendations from supervisors and fellow students. They adopted the Keenious tool to some extent, in creative ways, as part of the larger ecology of human and technological resources. Tutors' use of tools is a role model for the students, and tools the tutors use that prove useful have a greater potential to be used than other random tools. It also matters if the tools are easily accessible in the infrastructure they already have access to and if the results can be confirmed with people or tools they already have confidence in.The larger infrastructure the students use includes fellow students, tutors, teachers, Google, Google Scholar, Zotero, text-to-speech, and speech-to-text software. Keenious was used together with other literature search tools in some parts of the writing process but was not used systematically by any of the students. The reason for this may be that it was a new tool that the students had not started using in previous studies or writing processes and was not part of the established habits.Students found creative ways to combine the tools throughout the writing process. Our findings provide an opportunity to discuss whether the students develop practices that are not necessarily shared with the wider academic community of practice, and whether their use of the technology enables them to participate more competently in the community.With such changes in the students' information practices, where they explore AI-based aids and approaches, those who support the students in their information-related activities, such as tutors and library staff, will have to deal with the technology as a new type of actor. Library staff must not only provide introductions and guidance to the tools, but also help students understand the interaction with technology as an active participant in the writing process.
Keywords: artificial intelligence; information practices; writing tools